MODEL STABILISASI TANAH DASAR UNTUK DISPOSAL AREA KALI SEMARANG - Abdul Rochim (Majalah Ilmiah Sultan Agung, 2012)
This study presents the analysis of ground settlement and stabilisation that aims to estimate the soil types, ground settlement and stabilization of the soil in Disposal Area Semarang River. The data of the two soils from this area was used as samples to represent the average soil condition. A preloading model by applying five meter embankment was used to consolidate the soil. To estimate the immediate and consolidation settlement and the change of excess pore water pressure, PLAXIS application program was used. Based on the analysis from 30 meter soil layer of the two soil samples, it was shown that this area of Semarang River had the soil type SE or soft soil. Having the embankment as load, there was the settlement as big as 2.57-2.64 meters in which took 64.5 years to happen with the consolidation degree 90 per cent that was equal to the settlement 4 centimeters per year. From the stage constructions in PLAXIS, the result was reliable as to the increase of shear strength after consolidating. It was shown that there was the increase of shear strength amounting to 13 per cent from 282.61 kN/m2 (initial condition) to 318.75 kN/m2 (after consolidation). To decrease the time for soil to consolidate,  vertical and horizontal drains can be proposed. With the vertical drain having distance in between 1 meter and a triangle pattern, the time to reach the full settlement just 4.2 weeks. Key words :     Soil types, settlement, preloading, vertical drain, Disposal Area Kali Semarang